The War That Saved My Life - Kimberly Brubaker Bradley (Text Publishing Co Melbourne, Australia, 2016)
An exceptionally moving story of triumph against all odds, set during World War Two. Nine-year-old Ada has never left her one-room flat. Her mother is too humiliated by Ada's twisted foot to let her outside. So when her little brother Jamie is shipped out of London to escape the war, Ada doesn't waste a minute-she sneaks out to join him. So begins a new adventure for Ada, and for Miss Susan Smith, the woman who is forced to take in the two children. As Ada teaches herself to ride a pony, learns to read, and watches for German spies, she begins to trust Susan-and Susan begins to love Ada and Jamie. But in the end, will their bond be enough to hold them together through wartime? Or will Ada and her brother fall back into the cruel hands of their mother? This masterful work of historical fiction is equal parts adventure and a moving tale of family and identity-a classic in the making. a Praise for The War that Saved My Life- 'Achingly lovely...Nuanced and emotionally acute, this vivid tale from the wartime home front will have readers ages 10-14 wincing at Ada's stumbles and rejoicing to the point of tears in her victories.' Wall Street Journal a'Ada's voice is brisk and honest; her dawning realizations are made all the more poignant for their simplicity... Things come to an explosive head, metaphorically and literally. Ignorance and abuse are brought to light, as are the healing powers of care, respect and love. Set against a backdrop of war and sacrifice, Ada's personal fight for freedom and ultimate triumph are cause for celebration.' Kirkus, starred review 'Proving that her courage and compassion carry far more power than her disability, Ada earns self-respect, emerges a hero, and learns the meaning of home.' Publishers Weekly, starred review
Keywords: Historical Fiction